Retention of Ti Si snap versus locator attachments with retention sil in two-implant retained mandibular overdentures: an in vitro study. - Mourad, Dina; El-mahrouky, Nesrin A.; El-Dayem, Mohamed A. Abd; Shawky, Yasser M. (BMC Oral Health, 2025)
Background: Primary retention and progressive loss of retention of various attachment systems are critical elements in appropriate attachment selection; nevertheless, research on attachment retention reveals a broad spectrum of retention values for the same attachment system and between various systems. Accordingly, the aim of this study was to compare the retention of two different types of attachments (Ti Si snaps and locators) in two-implant-retained mandibular overdentures. Methods: A completely edentulous mandibular educational cast was scanned. An STL file including the implant beds and mucosal space was designed. Two implant analogs were incorporated into each model in the canine area bilaterally, and conventional overdentures were fabricated over two types of implant attachments, the Ti Si snap attachments and the locator attachments, with the use of Retention sil in both groups at the fitting surface of the overdenture. Each group contained five 3D-printed edentulous mandibular models. Retention was measured by using a universal testing machine after the models were subjected to cyclic loading. This measurement was carried out at the time of insertion, after 75,000 cycles (simulating 6 months of clinical use) and 150,000 cycles (simulating 12 months of clinical use). The means and standard deviations of the recorded readings were collected, tabulated, and statistically analyzed. Results: Student's t test revealed significant differences between the two groups. The Ti Si attachment group presented the highest retention rate at the time of insertion and after 6 months. However, there was no significant difference between the groups after 12 months. Both groups presented statistically significant changes in the mean retention value over time, as demonstrated by two-way ANOVA (time of insertion > six months > twelve months). Tukey's post hoc test revealed a nonsignificant difference between six months and twelve months. Conclusion: Within the limitations of this study, the following conclusions can be drawn: